Therapeutic Benefits of Whey Protein - jaafir, sadiq; mahdi, salah (University of Thi-Qar Journal of agricultural research, 2024)
Whey, a milk-based protein complex, is being promoted as a functional food with several health advantages. Alpha-lactalbumin, betalactoglobulin, lactoferrin, glycomacropeptide, and immunoglobulins are among the biological components of whey that exhibit a variety of immune-boosting characteristics. Whey can also function as a chelating agent, antiviral, antibacterial, hypolipidemic, antihypertensive, anticancer, and antioxidant. The conversion of the amino acid cysteine into glutathione, a strong intracellular antioxidant, is believed to be the main way that whey works. Whey has been successfully used in several clinical trials as an antibacterial agent and to treat cancer, HIV, hepatitis B, cardiovascular disease, and osteoporosis. Additionally, whey protein has shown promise in improving workout performance.